A medium-density genetic linkage map of the bovine genome - Barendse, W.; Vaiman, D.; Kemp, Stephen J.; Sugimoto, Y.; Armitage, S.M.; Williams, J.L.; Sun, H.S.; Eggen, A.; Agaba, Morris; Aleyasin, S.A.; Band, M.; Bishop, M.D.; et al. (Springer, 1997)
A cattle genetic linkage map was constructed which covers more than 95 percent of the bovine genome at medium density. Seven hundred and forty six DNA polymorphisms were genotyped in cattle families which comprise 347 individuals in full sibling pedigrees. Seven hundred and three of the loci are linked to at least one other locus. All linkage groups are assigned to chromosomes, and all are orientated with regards to the centromere. Them is little overall difference in the lengths of the bull and cow linkage maps although there are individual differences between maps of chromosomes. One hundred and sixty polymorphisms are in or near genes, and the resultant genome-wide comparative analyses indicate that while there is greater conservation of synteny between cattle and humans compared with mice, the conservation of gene order between cattle and humans is much less than would be expected from the conservation of synteny. This map provides a basis for high-resolution mapping of the bovine genome with physical resources such as Yeast and Bacterial Artificial Chromosomes as well as providing the underpinning for the interpolation of information from the Human Genome Project.